Immobilization of a model protein, BSA onto graphene oxide - Abdul Halim, C.R.A. Wahida Fazlina (2015)
This project was carried out to immobilize BSA protein onto nanomaterial, which is graphene oxide (GO). Two different methods have been used in order to immobilize this protein, the first method for immobilization is by physical adsorption and the second method is by chemical modification of GO using 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride-N-hydroxysuccinimide (EDC-NHS) as the crosslinker. The aim is for potential development of a GO-based immunoassay and to choose the best method to be used to immobilize BSA protein onto GO. Several parameters have been selected for the optimization in order to develop effective GO-based immunoassay such as amount of BSA to be immobilized, concentration of GO, and incubation time for BSA immobilization. Suitable GO concentration for BSA immobilization is 1 mg/ml, and 1 hour incubation time has been selected. For the amount of BSA, 0.5 mg is the sufficient amount of BSA that give a good electrochemical signal in CV measurement. For immobilization method, the chemical modification method is the best method to be used to immobilize BSA protein onto GO.